Meningkatkan Motivasi Belajar Peserta Didik dengan Menerapkan Model Reading Guide Berbasis PAIKEM - Lasiati, Lasiati (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
This research aimed to know effectiveness of implementing Guide Reading Model approach based PAIKEM in effort to improve students’ learning activities at second grade students of SD Negeri 4 Kuranji. Significant of this research was to be used as resources and invention in implementing of learning process at real classroom. For teachers it could be used to improve competence in learning process and for students it could be used to improve learning motivation which had impact in improving students’ achievement. This research was conducted in two cycles, acticities in every cycle was planning, acting, observing and reflecting. The result of final acting in cycle II showed that result of teachers’ observation got mean score (4,43) and mean score of students’ observation was (4,29). And result of improving students’ learning activities was improving result of students’ learning which got mean score (80,11), means indicator of completeness (> 75,00) was reached. Because indicator of completeness had proved so research was success and stopped in cycle II.